Legal Language – Pragmatic Approaches to Its Interconnectivity with Legal Interpretation and Legal Translation - Simonnaes, Ingrid (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
The purpose of this paper is to enhance existing insights into the complex relationship between legal language, legal interpretation and legal translation that challenges the participants of a particular domain-specific communicative situation. This situation can be described as a complex communicative-cognitive procedure taking into consideration a pragmatic approach to reach its addressees on a continuum from lay persons to experts.The analysis of some “typical” examples shows (not surprisingly) that different kinds of knowledge are necessary in order to achieve a felicitous communicative act in which a high degree of specialist knowledge is of paramount importance to a successful result both in intra- and interlingual translation.The particular legal language under scrutiny, in other words German contrastive to Norwegian, form the basis for the analysis of the activity of translation in which the translator must be able to understand/interpret the text and must be aware of not taking the words at their “face value” to be able to render their meaning in the target language.